EXPERIMENTAL SUBSTANTIATION OF APPLICATION OF ALLOGENIC COLLAGEN-FASCIAL GRAFT FOR SOFT TISSUE AUGMENTATION MAXILLOFACIAL - Kutsevlyak, V.I. (World of Medicine and Biology, 2016)
Contour face widespread in medical rehabilitation after serious injury of facial tissues, accompanied by a defect, after the ravages of cancer operations for congenital anomalies of development, lipo and muscular dystrophy, other acquired deformities of the face.Contour maxillofacial allogenic collagen-fascial graft is indicated for large deformations predominantly atrophy or loss of significant amount of soft tissue without the express damage or changes in the skin.
Keywords: contour; facial tissue; collagen abnormalities